How can health remain central post-2015 in a sustainable development paradigm? - Hill, Peter S (BioMed Central, 2014)
In two years, the uncompleted tasks of the Millennium Development Goals will be merged with the agenda articulated in the 2012 United Nations Conference on Sustainable Development. This process will seek to integrate economic development (including the elimination of extreme poverty), social inclusion, environmental sustainability, and good governance into a combined sustainable development agenda. The first phase of consultation for the post-2015 Sustainable Development Goals reached completion in the May 2013 report to the Secretary-General of the High-Level Panel of Eminent Persons on the Post-2015 Development Agenda. Health did well out of the Millennium Development Goal (MDG) process, but the global context and framing of the new agenda is substantially different, and health advocates cannot automatically assume the same prominence. This paper argues that to remain central to continuing negotiations and the future implementation, four strategic shifts are urgently required. Advocates need to reframe health from the poverty reduction focus of the MDGs to embrace the social sustainability paradigm that underpins the new goals. Second, health advocates need to speak—and listen—to the whole sustainable development agenda, and assert health in every theme and every relevant policy, something that is not yet happening in current thematic debates. Third, we need to construct goals that will be truly “universal”, that will engage every nation—a significant re-orientation from the focus on low-income countries of the MDGs. And finally, health advocates need to overtly explore what global governance structures will be needed to finance and implement these universal Sustainable Development Goals.